Konservasi dan Preservasi Artefak Tanah Liat Museum Blambangan Banyuwangi - Sandra, Ferika; Mudawamah, Nita Siti (BACA: Jurnal Dokumentasi dan Informasi, 2024)
The Banyuwangi Blambangan Museum has several masterpieces of clay artifacts, including four mattresses and five tablets. All conservation and preservation efforts, both managerial and technical, are carried out only by one person responsible for this museum, the head of the Blambangan Museum. This research aims to understand the conservation and preservation process of material and tablet artifacts at the Banyuwangi Blambangan Museum. The research method used is a qualitative approach with purposive sampling techniques, in which the selection of data sources is based on specific considerations that the researcher considers to have an in-depth understanding of the research object. The research result show that preventive conservation and curative care processes have been implemented. However, some obstacles have emerged, including limited human resources, limited conservation facilities, and the absence of particular spaces for conservation activities such as preservation and restoration The study combines archaeological conservation and preservation techniques with the theory of Harvey and Mahard. Based on the research, the eight preservation and conservation steps applied at the Blambangan Museum have been carried out well but are not yet optimal. Two have not been implemented due to insufficient manpower and limited resources.